Impact absorbing materials, resin particles and hollow particles
By using a specific design of hollow particle molding material, the shell layer is composed of acrylic and styrene-based resin, the problem of easy deformation and low energy absorption efficiency of polystyrene-based materials under repeated compression loads is solved, and high energy absorption and low permanent deformation over a wide range is achieved.
Patent Information
- Application Number
- JP2021067833
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-13
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2041-04-13
AI Technical Summary
The polystyrene-based bubble particle molding materials in the prior art are prone to deform under repeated compression loads and have low energy absorption efficiency, while the foam particle molding materials are prone to deform under small compression loads and have insufficient energy absorption efficiency.
A hollow particle molding material consisting of a shell layer and an inner hollow part is used. The shell layer is composed of a composite resin containing acrylic and styrene components. The particle diameter and the resin film thickness of the fusion part are within a specific range, ensuring that the material has high energy absorption efficiency over a wide range and reducing permanent deformation.
It improves energy absorption efficiency within a wide range, reduces permanent deformation, adapts to different degrees of compression load changes, and maintains the stability and energy absorption performance of the material.
Smart Images

Figure 0007624341000003 
Figure 0007624341000004 
Figure 0007624341000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an impact absorbing material, a resin particle, and a hollow particle. [Background technology]
[0002] Shock absorbing materials such as floor spacers, tibia pads, and bumper cores are incorporated inside automobiles. These types of shock absorbing materials are required to have properties such as being resistant to deformation when compressive loads are repeatedly applied, having excellent energy absorption efficiency, and being lightweight. Conventionally, polystyrene resin foamed bead moldings obtained by molding polystyrene resin foamed beads in a mold have been used as shock absorbing materials (for example, Patent Document 1).
[0003] Patent Document 2 also describes that a molded product made of hollow spherical thermoplastic foam particles having a particle size of 0.5 to 20 mm and an average particle skin thickness of 3 μm or more can be advantageously used as a bumper core material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-127796 A [Patent Document 2] Japanese Patent Application Publication No. 2-28225 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the polystyrene resin foamed bead molding described in Patent Document 1 has a large compression set. Therefore, depending on the application or shape of the polystyrene resin foamed bead molding, the molding may gradually deform when a compressive load is repeatedly applied. In addition, when the polystyrene resin foamed bead molding is compressed, the compressive load required for deformation of the molding increases as the amount of strain increases, and it has been desired to further improve the energy absorption efficiency when the amount of strain increases.
[0006] On the other hand, the molded article obtained by molding the foam particles in a mold of Patent Document 2 is easily deformed even by a small compressive load because the particle skin is easily buckled when a compressive load is applied. Therefore, the molded article obtained by molding the foam particles in a mold of Patent Document 2 has a problem that the energy absorption efficiency is low even when the amount of strain is small.
[0007] The present invention has been made in view of the above background, and aims to provide an impact absorbing material that has a small compression set and excellent energy absorption efficiency over a wide range of strain amounts, and resin particles and hollow particles for producing this impact absorbing material. [Means for solving the problem]
[0008] One aspect of the present invention is an impact absorbing material comprising a molded body obtained by molding hollow particles having an outer shell layer and a hollow portion surrounded by the outer shell layer, the shell layer has a resin film having a base resin that is a composite resin containing a (meth)acrylic acid ester component derived from a (meth)acrylic acid ester monomer and a styrene-based component derived from a styrene-based monomer, The apparent density ρ of the shock absorbing material is 20 kg / m 3 More than 100kg / m 3 is as follows: The average particle diameter D of the hollow particles in the impact absorbing material is 2 mm or more and 9 mm or less, The impact absorbing material has a fused portion formed by fusing the outer shell layers of the hollow particles to each other, and the average value t of the total thickness of the resin film in the fused portion r is 80μm or more and 400μm or less the law of nature, The average thickness of the fused portion t t is more than 100 μm and 700 μm or less, The average thickness of the fused portion t t [μm] vs. the average total thickness of the resin film in the fused portion t r [μm] ratio t r / t t is between 0.3 and 0.9 , in shock absorbing material. Effect of the Invention
[0009] The impact absorbing material is composed of a molded body obtained by molding the specific hollow particles in a mold. The apparent density ρ of the impact absorbing material, the average particle diameter D of the hollow particles, and the average value t of the total thickness of the resin film in the fused portion r are each within the above-mentioned specific range. The impact absorbing material has such a configuration, and thus the compression set can be reduced. In addition, the impact absorbing material can appropriately increase the compression load required for deformation in the initial stage of compression. This can improve the energy absorption efficiency of the impact absorbing material when the amount of strain is small.
[0010] Furthermore, the impact absorbing material can reduce the difference between the compressive load required for deformation when the strain amount is small and the compressive load required for deformation when the strain amount is large, thereby improving the energy absorption efficiency even when the strain amount is large.
[0011] As a result, according to the above-mentioned embodiment, it is possible to provide an impact absorbing material which has a small compression set and excellent energy absorption efficiency over a wide range of strain amounts. [Brief description of the drawings]
[0012] [Figure 1]FIG. 1 is a cross-sectional view of the impact absorbing material of the first embodiment. [Diagram 2] FIG. 2 is an electron microscope photograph of the fusion-bonded portion in the impact absorbing material of Example 1, observed at a magnification of 200 times. [Diagram 3] FIG. 3 is an electron microscope photograph (magnification: 30 times) of the hollow particle in Example 1 in a state where it is divided into two. [Figure 4] FIG. 4 is an electron microscope photograph (magnification: 1000 times) showing an enlarged view of the outer shell layer in FIG. [Diagram 5] FIG. 5 is an electron microscope photograph (magnification: 30 times) of an expanded bead in a reference example in a state where the expanded bead was divided into two. [Figure 6] FIG. 6 is an explanatory diagram showing a method for calculating the energy absorption efficiency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (shock absorbing material) The impact absorbing material is composed of a molded body formed by molding hollow particles having an outer shell layer and a hollow portion surrounded by the outer shell layer in a mold. The hollow particles have an outer shell layer and a hollow portion surrounded by the outer shell layer. The outer shell layer constitutes the outer shell of the hollow particles and has a resin film made of a base resin. The outer shell layer may be composed of a single resin film. In addition, minute air bubbles partitioned by the resin film may be present in the outer shell layer. The structure of the hollow particles will be described in more detail later.
[0014] The shock absorbing material is used, for example, in automobile materials, building materials, logistics materials, cushioning materials, bedding, etc. The shock absorbing material is suitable for automobile materials, for example, floor spacers, tibia pads, door pads, bumpers, etc. In particular, shock absorbing materials in automobile materials must adequately absorb the large impact generated during a collision and reduce the impact acceleration generated in the occupants. The shock absorbing material of the present invention has excellent energy absorption efficiency over a wide range of strain amounts, and therefore has excellent suitability as floor spacers, tibia pads, door pads, and bumpers for vehicles, and is particularly suitable as floor spacers and tibia pads.
[0015] The impact absorbing material is composed of hollow particles, but may contain particles other than hollow particles as long as the above-mentioned action and effect are not impaired. Examples of particles other than hollow particles include foamed particles and particles that do not have a hollow structure. When particles other than hollow particles are contained in the impact absorbing material, the ratio of particles other than hollow particles in the impact absorbing material is preferably 40% or less, more preferably 30% or less, even more preferably 20% or less, and particularly preferably 10% or less. By increasing the ratio of hollow particles in the impact absorbing material, the compression set can be easily reduced. In addition, by increasing the ratio of hollow particles in the impact absorbing material, the rate of increase in compression load accompanying an increase in the amount of strain can be reduced. As a result, the energy absorption efficiency of the impact absorbing material can be improved even when the amount of strain is large.
[0016] The ratio of particles other than hollow particles in the impact absorbing material is a value expressed as a percentage (unit: %) of the number of particles other than hollow particles to the total number of particles in any cut surface of the impact absorbing material. The calculation method of the ratio of particles other than hollow particles in the impact absorbing material is specifically as follows. First, three or more positions from which slices are taken are randomly selected from the skin surface of the molded body of the impact absorbing material, that is, from the part excluding the vicinity of the surface that was in contact with the mold during in-mold molding, and slices with a thickness of about 2 mm are cut out at the selected positions. A scanner or the like is used to obtain a photograph of the surface of each slice, that is, the cross section of the impact absorbing material. A measurement area is set on each photograph obtained in this way so that 100 or more particles are included. The ratio of the total number of particles other than hollow particles to the total number of particles in these measurement areas is taken as the ratio of particles other than hollow particles in the impact absorbing material.
[0017] [apparent density ρ] The apparent density ρ of the shock absorbing material is 20 kg / m 3 More than 100kg / m 3 By setting the apparent density ρ of the impact absorbing material in the above-mentioned specific range, the compressive load required for deformation of the impact absorbing material in the initial stage of compression can be appropriately increased. As a result, the energy absorption efficiency of the impact absorbing material when the amount of strain is small can be improved. From the viewpoint of further enhancing this effect, the apparent density ρ of the impact absorbing material is set to 25 kg / m 3 It is preferable that the density is 30 kg / m or more. 3 It is more preferable that the apparent density ρ of the impact absorbing material is 80 kg / m or more. 3 It is preferable that the thickness is less than 60 kg / m 3 More preferably, it is 50 kg / m or less. 3 It is more preferable that the weight of the impact absorbing material is equal to or less than 100 g / m2. In this case, the weight of the impact absorbing material can be reduced more easily.
[0018] If the apparent density ρ of the impact absorbing material is too low, the mechanical properties such as rigidity may be lower than the range required for the impact absorbing material. If the apparent density ρ of the impact absorbing material is too high, the mass of the impact absorbing material may be excessively large. In this case, the rate of increase in the compression load required for deformation of the impact absorbing material tends to increase as the strain amount increases. Therefore, there is a risk of a decrease in the energy absorption efficiency when the strain amount is large.
[0019] [Average particle diameter of hollow particles D] The average particle diameter D of the hollow particles in the impact absorbing material is 2.0 mm or more and 9.0 mm or less. By setting the average particle diameter D of the hollow particles within the above-mentioned specific range, the total thickness of the resin film in the fusion part can be easily increased. And, by increasing the total thickness of the resin film, the rate of increase in the compression load associated with an increase in the amount of strain can be reduced. As a result, the difference between the compression load required for deformation when the amount of strain is small and the compression load required for deformation when the amount of strain is large can be reduced, and the energy absorption efficiency of the impact absorbing material can be improved in a wide range of the amount of strain. From the viewpoint of further enhancing such an effect, the average particle diameter D of the hollow particles is preferably 3.0 mm or more, more preferably 3.5 mm or more. Moreover, the average particle diameter D of the hollow particles is more preferably 8.0 mm or less, and even more preferably 6.0 mm or less. In this case, the filling property of the hollow particles into the molding die during in-mold molding can be further improved, and the variation in the physical properties of the obtained impact absorbing material can be further reduced.
[0020] The method for measuring the average particle diameter D of the hollow particles described above is as follows. First, the impact absorbing material is cut along the thickness direction, etc., to expose the cross section of the impact absorbing material. A cross-sectional photograph of the impact absorbing material thus exposed is taken, and in the cross-sectional photograph obtained, five or more lines are drawn randomly from one edge of the cross-sectional photograph along the thickness direction, etc., of the molded body to the opposite edge. Next, the length of the lines is measured, and the number of particles intersecting with the lines is counted. The total length of the lines is then divided by the total number of particles intersecting with the lines to obtain the average particle diameter D of the hollow particles.
[0021] [Other particles] The impact absorbing material may contain particles other than the hollow particles as long as the above-mentioned action and effect is not impaired. Examples of other particles include expanded particles having a cell structure in which a large number of bubbles are formed relatively uniformly throughout the particle.
[0022] [Fused part] The impact absorbing material has a fused portion formed by fusing the outer shell layers of the hollow particles together. The fused portion is composed of the outer shell layer of the hollow particle and the outer shell layer of the hollow particle adjacent to the hollow particle. The fused portion is usually in the shape of a flat plate.
[0023] ·Average total thickness of resin film t r Average total thickness of resin film in fusion zone t r The average total thickness of the resin film is t r By making the average total thickness t of the resin film 80 μm or more, the compression load required for deformation of the impact absorbing material in the initial stage of compression can be appropriately increased. r The average total thickness t of the resin film is preferably 85 μm or more, and more preferably 90 μm or more. r If t is too small, the energy absorption efficiency may decrease when the strain is large. rIf is excessively small, in addition to the decrease in the energy absorption efficiency when the strain amount is large, there is also a risk of a decrease in the energy absorption efficiency when the strain amount is small.
[0024] In addition, the average total thickness of the resin film t r By making the average total thickness t of the resin film 400 μm or less, preferably 300 μm or less, more preferably 250 μm or less, and further preferably 200 μm or less, it is possible to further improve the energy absorption efficiency of the impact absorbing material while ensuring a low apparent density ρ. r If is excessively large, the apparent density ρ of the impact absorbing material becomes high, which may lead to an increase in the mass of the impact absorbing material.
[0025] Average total thickness of resin film t r The calculation method for is as follows. First, the impact absorbing material is cut at an appropriate position to expose the cut surface. Using a scanning electron microscope, 30 or more fusion parts to be observed are randomly selected from the multiple fusion parts that appear on the cut surface. These fusion parts are observed at an appropriate magnification (for example, 200 times magnification) to obtain enlarged photographs of each fusion part.
[0026] Next, on the fused portion in each enlarged photograph, a line segment extending in the thickness direction of the fused portion is drawn from one surface of the fused portion to the other surface of the fused portion.
[0027] The above operation is carried out at 10 or more positions randomly selected from each enlarged photograph, the length of the line segments extending in the thickness direction of the fused portion is measured, and the length of the portion of each line segment that overlaps with an air bubble is calculated. Next, the length of the portion that overlaps with an air bubble is subtracted from the length of each line segment, and these values are arithmetically averaged to calculate the total thickness of the resin film at each fused portion. Then, the above-mentioned total thickness of the resin film is calculated for the 30 or more fused portions that were observed, and the arithmetic average value of these total thicknesses of the resin film is taken as the average total thickness of the resin film at the fused portions, t r Let us assume that.
[0028] Average thickness of fused part t t Average thickness of fused part t t The average total thickness t of the resin film in the fused portion is preferably more than 100 μm and not more than 700 μm. r is within the above-mentioned specific range, and the average thickness t of the fused portion is t By setting the average thickness t of the fused portion within the above-mentioned specific range, the rate of increase in the compressive load accompanying an increase in the amount of strain can be more reliably reduced. As a result, the energy absorption efficiency of the impact absorbing material when the amount of strain is large can be more reliably improved. From the viewpoint of further enhancing this effect, t is more preferably 120 μm or more, and further preferably 130 μm or more.
[0029] In addition, the average thickness of the fused part t t is more preferably 500 μm or less, further preferably 400 μm or less, and particularly preferably 300 μm or more. In this case, even if the shape of the impact absorbing material is complicated, it is possible to more easily obtain an impact absorbing material having excellent appearance and good physical properties.
[0030] Average thickness of fused part t t The calculation method is as follows. First, the average value of the total thickness of the resin film mentioned above, t t In the same manner as in the calculation method of (a), 30 or more fused portions randomly selected from the cut surface of the impact absorbing material are observed under a scanning electron microscope, and enlarged photographs of each fused portion are obtained.
[0031] Next, on the fused portion in each enlarged photograph, a line segment extending in the thickness direction of the fused portion is drawn from one surface of the fused portion to the other surface of the fused portion.
[0032] The above operation is carried out at 10 or more randomly selected positions in each enlarged photograph, and the length of the line segment extending in the thickness direction of the fused portion is measured. The arithmetic mean value of the lengths of these line segments is then taken as the thickness of the fused portion shown in the enlarged photograph. This operation is carried out for each of the 30 or more fused portions observed, and the arithmetic mean value of the thicknesses of the fused portions obtained is taken as the average thickness t t Let us assume that.
[0033] Average thickness of fused part t t (Unit: μm) Average total thickness of resin film in fusion area t r (unit: μm) ratio t r / t t The average total thickness of the resin film in the fused portion t is preferably 0.3 or more and 1 or less. r is within the specified range, and t r / t t By setting the value of t in the above-mentioned specific range, the rate of increase in the compressive load accompanying an increase in the amount of strain can be more reliably reduced. As a result, the energy absorption efficiency of the impact absorbing material when the amount of strain is large can be more reliably improved. From the viewpoint of stably achieving this effect, the ratio t r / t t is more preferably 0.4 or more, and even more preferably 0.5 or more.
[0034] In addition, the average thickness of the fused part t t The average total thickness of the resin film in the fusion zone, t r The ratio of t r / t t is more preferably 0.9 or less, and even more preferably 0.8 or less. In this case, the rate of increase in the compressive load accompanying an increase in the amount of strain can be further reduced, and the energy absorption efficiency of the impact absorbing material when the amount of strain is large can be further improved. t The average total thickness of the resin film in the fusion zone t r The ratio of t r / t tA value of 0.9 or less means that air bubbles are contained in the fused part, and it is considered that the proportion of an increase in compressive load relative to an increase in strain can be made gentler by having the fused part have a structure that contains a moderate amount of air bubbles.
[0035] Apparent density ρ of shock absorbing material (unit: kg / m 3 ) Average total thickness of resin film in fusion area t r (unit: μm) ratio t r / ρ (unit: μm / (kg / m 3 ) is preferably 2.0 or more and 8.0 or less. In this case, the mass of the impact absorbing material can be easily reduced, and the energy absorption efficiency of the impact absorbing material can be improved when the amount of strain is large.
[0036] Compressive Stress The energy absorption characteristics of an impact absorbing material can be evaluated based on the magnitude of compressive stress at various strains. a The energy absorption efficiency of the shock absorbing material in is calculated by the time ε a The closer the shape of the stress-strain curve is to a rectangle, the higher the strain. a Compressive stress σ a and strain amount ε a A strain amount ε smaller than b Compressive stress σ b The smaller the difference between the stress and strain, the closer the shape of the stress-strain curve is to a rectangle, and the smaller the strain amount ε a It can be said that the energy absorption efficiency of the impact absorbing material is high.
[0037] From this perspective, the 50% deformation compressive stress σ of the impact absorbing material at 23°C 50 (Unit: kPa) vs. 75% deformation compressive stress σ at 23℃ 75 Ratio σ (unit: kPa) 75 / σ 50is preferably 1.0 or more and less than 2.0. In this case, the energy absorption efficiency when the amount of strain is large can be improved, and even when a large impact is applied to the impact absorbing material, the impact energy can be absorbed while protecting the protected object.
[0038] In addition, the 75% deformation compressive stress σ of the impact absorbing material at 23℃ 75 (Unit: kPa) vs. 10% deformation compressive stress σ at 23℃ 10 Ratio σ (unit: kPa) 10 / σ 75 is preferably 0.30 or more and 1.0 or less. In this case, the energy absorption efficiency of the impact absorbing material can be improved over a wider range of strain amounts.
[0039] From a similar perspective, the 50% deformation compressive stress σ of the impact absorbing material at 23℃ 50 (Unit: kPa) vs. 25% deformation compressive stress σ at 23℃ 25 Ratio σ (unit: kPa) 25 / σ 50 is preferably 0.50 or more and 1.0 or less.
[0040] [Compression set] The compression set of the impact absorbing material is preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less. Impact absorbing materials having such characteristics are less likely to accumulate permanent set even when compressive loads are repeatedly applied, and can easily restore to their pre-compression shape. Therefore, impact absorbing materials with compression set within the above specific range can maintain excellent energy absorption properties for a longer period of time even when compressive loads are repeatedly applied.
[0041] (Method of manufacturing impact absorbing material) The impact absorbing material is manufactured, for example, as follows. First, the hollow particles are filled into a mold having a cavity corresponding to the shape of the desired impact absorbing material. At this time, the particle group filled into the mold may contain particles other than hollow particles in addition to hollow particles. When the particle group filled into the mold contains particles other than hollow particles, the ratio of hollow particles in the particle group is preferably 50% or more, more preferably 60% or more, even more preferably 80% or more, and particularly preferably 90% or more. Next, the hollow particles in the mold are heated by a heating medium such as steam. The hollow particles expand and fuse to each other by being heated in the cavity. At this time, the outer shell layer of the hollow particle and the outer shell layer of the hollow particle next to the hollow particle are fused to each other to form a fused part. As a result, a molded body having a shape corresponding to the shape of the cavity and composed of hollow particles is obtained. The molded body obtained in this way may be used as an impact absorbing material as it is. If necessary, the molded article may be subjected to cutting or other processing to be molded into a desired shape, and the molded article may be used as an impact absorbing material.
[0042] (hollow particles) The hollow particles used in the manufacture of the impact absorbing material have an outer shell layer and a hollow portion surrounded by the outer shell layer. The hollow particles of the present invention are hollow particles obtained by expanding resin particles containing an organic physical foaming agent described below. The hollow particles of the present invention have a structure different from that of expanded particles having a cell structure in which a large number of bubbles are formed relatively uniformly throughout the particle. It is preferable that the hollow particles before molding in a mold are spherical.
[0043] The hollow part of the hollow particle is located closer to the center of the hollow particle than the outer shell layer. The hollow part, i.e., the region surrounded by the outer shell layer, may be substantially hollow. Here, "substantially hollow" refers to a state in which the structure of the outer shell layer and the structure of the hollow part are clearly different when the hollow particle is cut at a cross section passing through its center and the cut surface is observed at a magnification of 20 to 1000 times using a transmission electron microscope or the like.
[0044] For example, the hollow portion may be a single space separated from the outside of the hollow particle by the shell layer. The hollow portion may also have a space wall that is made of a base resin and divides the hollow portion into a plurality of spaces. In this case, the hollow portion may have several to several tens of spaces divided by the space wall of the hollow portion or by the space wall of the hollow portion and the inner surface of the shell layer. From the viewpoint of easily expressing the desired physical properties, it is preferable that the hollow portion is divided into 50 or less spaces, more preferably into 30 or less spaces, even more preferably into 10 or less spaces, and particularly preferably into 5 or less spaces, in a cross section when the hollow particle is divided into two equal parts.
[0045] If the region surrounded by the shell layer of the hollow particles is substantially hollow, a molded body having the desired physical properties can be obtained by molding in a mold, and an impact absorbing material having a small compression set and excellent energy absorption efficiency over a wide range of strain can be manufactured. The hollow part of the hollow particles is preferably a single space separated from the outside of the hollow particles by the shell layer. For the structure and hollow part of the hollow particles in the molded body after molding in a mold, the structure and hollow part of the hollow particles used in the manufacture of the molded body can be appropriately referred to.
[0046] [Average particle size] The average particle size of the hollow particles before molding in a mold is preferably 2.0 mm or more and 9.0 mm or less. By molding hollow particles having an average particle size in the specific range in a mold, the average particle size of the hollow particles in the impact absorbing material can be easily adjusted to fall within the specific range.
[0047] The average particle size of the hollow particles before molding is the cumulative 63% diameter (i.e., d63) calculated based on the particle size distribution of the hollow particles on a volume basis. The particle size distribution of the hollow particles on a volume basis can be obtained using a particle size distribution measuring device (for example, "Militrack JPA" manufactured by Nikkiso Co., Ltd.).
[0048] [Bulk density] The bulk density of the hollow particles before molding is 20 kg / m 3 More than 100kg / m 3 It is preferable that the bulk density of the hollow particles is 22 kg / m or less. The hollow particles having the hollow structure described above and a bulk density in the specific range are lightweight and excellent in both rigidity and recovery. Therefore, by molding hollow particles having such a bulk density in a mold, it is possible to easily obtain an impact absorbing material that is lightweight, has a small compression set, and has excellent energy absorption efficiency over a wide range of strain amounts. From the viewpoint of increasing the rigidity and recovery of the hollow particles, the bulk density of the hollow particles before molding in a mold is preferably 22 kg / m or less. 3 More preferably, it is 25 kg / m or more. 3 More preferably, it is equal to or greater than this.
[0049] In order to further improve the light weight of the hollow particles, the bulk density of the hollow particles before molding is set to 80 kg / m 3 More preferably, it is 60 kg / m or less. 3 More preferably, it is 50 kg / m or less. 3 It is particularly preferred that:
[0050] The bulk density of hollow particles mentioned above is a value calculated by the following method. First, an arbitrary amount of hollow particles is prepared as the measurement object. The condition of the measurement object is adjusted by leaving the measurement object for 10 days under conditions of 50% relative humidity, 23°C temperature, and 1 atm. The measurement object is allowed to naturally pile up in a measuring cylinder, and then a light impact is applied to the bottom of the measuring cylinder to stabilize the filling height of the measurement object in the measuring cylinder. The bulk volume (unit: L) of the measurement object indicated by the graduations on the measuring cylinder is then read. The mass (unit: g) of the measurement object placed in the measuring cylinder is divided by the bulk volume, and the units are then converted. From the above, the bulk density (unit: kg / m) of the hollow particles is calculated. 3 ) can be obtained.
[0051] [Outer shell layer] The outer shell layer of the hollow particle has a resin film made of a base resin and a plurality of bubbles partitioned by the resin film. The outer shell layer may have a multi-layer structure including, for example, a solid lower layer facing the hollow portion, a solid upper layer exposed on the outermost surface of the hollow particle (i.e., the outer surface of the outer shell layer), and a foam layer having a plurality of bubbles and located between the lower layer and the upper layer. Here, the solid means a state in which there are substantially no bubbles in the resin.
[0052] The average total thickness of the resin film in the hollow particles before molding is preferably 30 μm or more, more preferably 35 μm or more, and even more preferably 40 μm or more. By molding such hollow particles in a mold, a molded body having a moderately high compression load required for deformation in the initial stage of compression and high energy absorption efficiency when the amount of strain is large can be more easily obtained. In addition, the average total thickness of the resin film in the hollow particles is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 120 μm. In this case, a molded body having a low apparent density and excellent energy absorption efficiency can be more easily obtained.
[0053] The average thickness of the shell layer in the hollow particles before molding is preferably more than 50 μm and 350 μm or less. In addition, the ratio of the average value of the total thickness of the resin film to the average thickness of the shell layer in the hollow particles before molding is preferably 0.3 or more, more preferably 0.5 or more. By making the structure of the shell layer a structure specified by the above-mentioned average thickness and the ratio of the average value of the total thickness of the resin film to the average thickness of the shell layer, the durability of the shell layer against load can be improved. This can increase the restorability of the hollow particles against repeated load.
[0054] From the viewpoint of further improving the restorability of the hollow particles, the average thickness of the outer shell layer in the hollow particles before molding is more preferably 60 μm or more, and even more preferably 70 μm or more. From the same viewpoint, the ratio of the average value of the total thickness of the resin film to the average thickness of the outer shell layer in the hollow particles before molding is more preferably 0.50 or more, and even more preferably 0.55 or more.
[0055] The average thickness of the outer shell layer is a value calculated by the following method. First, the hollow particles before molding in a mold are divided into roughly two equal parts to expose the cut surface of the outer shell layer. Using a scanning electron microscope, three or more observation positions are set randomly within one of the roughly four equal parts of the cut surface of the outer shell layer. These observation positions are observed at an appropriate magnification (for example, 1000 times magnification) to obtain enlarged photographs of the cut surface of the outer shell layer at each observation position.
[0056] On the outer shell layer in the enlarged photograph obtained, a line segment extending in the thickness direction of the outer shell layer (i.e., the radial direction of the hollow particle) is drawn from the outer surface to the inner surface of the outer shell layer. The above operation is performed at 10 or more positions randomly selected from each enlarged photograph, and the length of the line segment is measured at a total of 30 or more positions. The arithmetic mean value of the lengths of the line segments thus obtained is regarded as the thickness of the outer shell layer of each hollow particle. Then, the aforementioned thickness of the outer shell layer is calculated for 5 or more randomly selected hollow particles, and the arithmetic mean value of these shell layer thicknesses is regarded as the average thickness of the outer shell layer.
[0057] In calculating the average total thickness of the resin film of the shell layer of the hollow particles before molding, in the same manner as in the calculation method of the average thickness of the shell layer, the cut surface of the shell layer is divided into approximately four equal parts, and three or more observation positions are set randomly for one of the regions, and an enlarged photograph of the cut surface of the shell layer at each observation position is obtained. Next, on the shell layer in each enlarged photograph, a line extending in the thickness direction of the shell layer is drawn from the outer surface of the shell layer to the inner surface of the shell layer.
[0058] The above operation is carried out at 10 or more randomly selected positions in each enlarged photograph, the length of the line segment extending in the thickness direction of the outer shell layer is measured, and the length of the portion of each line segment overlapping with the air bubble is calculated. Next, the length of the portion overlapping with the air bubble is subtracted from the length of each line segment, and these values are arithmetically averaged to calculate the total thickness of the resin film of each hollow particle. Then, the total thickness of the resin film described above is calculated for 5 or more randomly selected hollow particles, and the arithmetic average value of these total thicknesses of the resin film is regarded as the average total thickness of the resin film.
[0059] [Base resin] The base resin of the resin film in the hollow particle is a composite resin containing a (meth)acrylic acid ester component derived from a (meth)acrylic acid ester monomer and a styrene-based component derived from a styrene-based monomer. As described later, the composite resin is preferably a composite resin obtained by impregnating and polymerizing a core particle having a styrene-based resin as a base resin with a (meth)acrylic acid ester monomer and a styrene-based monomer.
[0060] Examples of the (meth)acrylic acid ester component contained in the composite resin include components derived from acrylic acid ester monomers such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate, and components derived from methacrylic acid ester monomers such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, and 2-ethylhexyl methacrylate. The composite resin may contain one or more components selected from these (meth)acrylic acid ester components.
[0061] The composite resin preferably contains a component derived from methyl methacrylate as the (meth)acrylic acid ester component. In this case, the content of the component derived from methyl methacrylate in the (meth)acrylic acid ester component is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. In this case, the structure and physical properties of the hollow particles can be more reliably made to be the desired structure and physical properties.
[0062] Examples of styrene-based components contained in the composite resin include components derived from styrene-based monomers such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-methoxystyrene, pn-butylstyrene, pt-butylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,4,6-tribromostyrene, divinylbenzene, styrene sulfonic acid, and sodium styrene sulfonate, components derived from homopolymers of styrene-based monomers such as polystyrene, components derived from copolymers of styrene-based monomers and other monomers or polymers such as rubber-modified polystyrene, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-ethylene propylene rubber-styrene copolymer. The composite resin may contain one component selected from these styrene-based components, or may contain two or more components.
[0063] The composite resin preferably contains a component derived from styrene as the styrene-based component. In this case, the content of the component derived from styrene in the styrene-based component is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. In this case, the structure and physical properties of the hollow particles can be more reliably made to be the desired structure and physical properties.
[0064] The composite resin may contain components other than the (meth)acrylic acid ester component and the styrene-based component, such as components derived from monomers having a carbon-carbon double bond, such as vinyl compounds containing a hydroxyl group, vinyl compounds containing a nitrile group, organic acid vinyl compounds, olefin compounds, diene compounds, vinyl halides, vinylidene halides, and maleimide compounds.
[0065] Examples of vinyl compounds containing a hydroxyl group include hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, etc. Examples of vinyl compounds containing a nitrile group include acrylonitrile, methacrylonitrile, etc.
[0066] Examples of the organic acid vinyl compound include vinyl acetate and vinyl propionate. Examples of the olefin compound include ethylene, propylene, 1-butene, and 2-butene. Examples of the diene compound include butadiene, isoprene, and chloroprene.
[0067] Examples of the vinyl halide compound include vinyl chloride, vinyl bromide, etc. Examples of the vinylidene halide compound include vinylidene chloride, etc. Examples of the maleimide compound include N-phenylmaleimide, N-methylmaleimide, etc.
[0068] The composite resin may contain one type of component selected from the components derived from these monomers having a carbon-carbon double bond, or may contain two or more types of components.
[0069] The amount of the other components other than the (meth)acrylic acid ester component and the styrene-based component is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the total of the (meth)acrylic acid ester component and the styrene-based component. In this case, the structure and physical properties of the hollow particles can be more reliably made to be the desired structure and physical properties.
[0070] The composite resin can be obtained, for example, by impregnating and polymerizing a core particle having a styrene-based resin as a base resin with a (meth)acrylic acid ester monomer and a styrene-based monomer. As the styrene-based resin that can be used to prepare the composite resin, a homopolymer of the above-mentioned styrene-based monomer, a copolymer of the styrene-based monomer with another monomer or polymer, etc. can be used.
[0071] The weight average molecular weight of the composite resin is 30×10 4 More than 50 x 10 4 Preferably, it is 35×10 or less. 4 Over 45×10 4 It is more preferable that the weight average molecular weight is not more than 1000g / mol. In this case, the rigidity and restorability of the hollow particles can be further improved. The weight average molecular weight of the composite resin is a polystyrene-equivalent molecular weight measured by gel permeation chromatography using polystyrene as a standard substance.
[0072] The mass ratio of the (meth)acrylic ester component to the styrene-based component contained in the composite resin is preferably (meth)acrylic ester component:styrene-based component=70:30 to 30:70, and more preferably (meth)acrylic ester component:styrene-based component=60:40 to 40:60. In this case, the yield of hollow particles having the specific structure can be further increased.
[0073] In addition, when a composite resin is produced by impregnating and polymerizing a core particle composed of a base resin containing a (meth)acrylic acid ester component and / or a styrene-based component with a (meth)acrylic acid ester monomer and / or a styrene-based monomer, the mass ratio of the (meth)acrylic acid ester component and the styrene-based component contained in the composite resin can be determined from the relationship between the mass of each component in the core particle and the mass of each monomer to be impregnated and polymerized.
[0074] [Additives] The hollow particles may contain additives such as a cell regulator, a catalyst neutralizer, a lubricant, a crystal nucleating agent, an antistatic agent, etc., within the range that does not impair the above-mentioned action and effect. The content of the additives in the hollow particles is, for example, preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, and particularly preferably 5% by mass or less, based on the total mass of the hollow particles.
[0075] (Resin particles) The hollow particles are obtained by expanding resin particles having the following structure: the resin particles have a base resin that is a composite resin containing a (meth)acrylic acid ester component derived from a (meth)acrylic acid ester monomer and a styrene-based component derived from a styrene-based monomer, and contain an organic physical foaming agent; The average particle size of the resin particles is 1 mm or more and 5 mm or less, a mass ratio of the (meth)acrylic acid ester component to the styrene-based component contained in the composite resin is (meth)acrylic acid ester component:styrene-based component=70:30 to 30:70; In an infrared absorption spectrum of the surface of the resin particle obtained by a total reflection measurement method, the value of the surface absorbance ratio S represented by the following formula (1) is 0.70 or more. S=As acryl / As styrene (1)
[0076] However, As in the formula (1) styrene is 650cm -1 More than 750cm -1The maximum absorbance in the range below is As acryl The wave number is 1680 cm -1 over 1780cm -1 The maximum absorbance in the following range:
[0077] The base resin in the resin particles is the same as the base resin in the hollow particles described above.
[0078] As the organic physical blowing agent, for example, a volatile organic compound having a boiling point of 90° C. or less at atmospheric pressure, such as propane, normal butane, isobutane, normal pentane, isopentane, neopentane, hexane, cyclobutane, cyclopentane, dimethyl ether, diethyl ether, etc. These volatile organic compounds may be used alone, or two or more kinds of volatile organic compounds may be used in combination.
[0079] The content of the organic physical blowing agent in the resin particles is preferably 3% by mass or more and 8% by mass or less, and more preferably 4% by mass or more and 7% by mass or less, which can increase the yield of hollow particles having a desired structure.
[0080] In the infrared absorption spectrum of the surface of the resin particle obtained by the total reflection measurement method, the value of the surface absorbance ratio S represented by the above formula (1) is 0.70 or more. styrene is the intensity of the peak due to the out-of-plane bending vibration of the benzene ring contained in the styrene-based component. acryl is the intensity of the peak derived from the C=O stretching vibration of the carbonyl group contained in the (meth)acrylic acid ester component.
[0081] Therefore, the value of the surface absorbance ratio S represented by the formula (1) is related to the ratio of the styrene-based component and the (meth)acrylic acid ester component present on the surface of the resin particle. The (meth)acrylic acid ester component is abundantly present on the surface of the resin particle having the surface absorbance ratio S value within the specific range. By expanding such resin particles, hollow particles having the desired structure and properties can be easily obtained. From the viewpoint of more reliably obtaining hollow particles having a good hollow structure, the upper limit of the value of the surface absorbance ratio S represented by the formula (1) is preferably about 3.0, more preferably 2.0, and even more preferably 1.5. If the value of the surface absorbance ratio S is too low, it may be difficult to obtain hollow particles having the desired outer shell structure when the resin particles are expanded.
[0082] The method for calculating the surface absorbance ratio S is specifically as follows. First, a diamond prism with an incident angle of 45 degrees is placed on resin particles with a pressure of 170 kg / cm 2 The uncorrected infrared absorption spectrum is obtained by pressing the sample with a pressure of 1000 cm. The absorbance of the obtained infrared absorption spectrum is calculated based on the penetration depth of the infrared light at each wave number. -1 The entire spectrum is corrected so that it coincides with the penetration depth of infrared light of . Based on the corrected infrared absorption spectrum obtained in this way, the maximum absorbance As is calculated. styrene and As acryl Then, As acryl The value of As styrene The value obtained by dividing the absorbance by the surface absorbance ratio S is
[0083] In addition, it is preferable that the ratio S / I between the surface absorbance ratio S represented by the above formula (1) and the internal absorbance ratio I represented by the following formula (2) in the infrared absorption spectrum of the inside of the resin particle obtained by total reflection measurement method is 0.3 or more and 3 or less. I=Ai acryl / Ai styrene (2)
[0084] However, Ai in the above formula (2) styreneis 650cm -1 More than 750cm -1 The maximum absorbance in the range below, Ai acryl The wave number is 1680 cm -1 over 1780cm -1 The maximum absorbance in the following range:
[0085] The maximum absorbance Ai in the above formula (2) styrene is the maximum absorbance value As in equation (1). styrene Similarly, it is the intensity of the peak due to the out-of-plane bending vibration of the benzene ring contained in the styrene-based component. acryl is the maximum absorbance value As in equation (1). acryl Similarly, it is the intensity of the peak derived from the C=O stretching vibration of the carbonyl group contained in the (meth)acrylic acid ester component.
[0086] Therefore, the value of the internal absorbance ratio I represented by the above formula (2) is related to the ratio of the styrene-based component and the (meth)acrylic acid ester component present inside the resin particle. And the ratio S / I of the surface absorbance ratio S to the internal absorbance ratio I is related to the ratio of the concentration of the styrene-based component inside the resin particle to the concentration of the styrene-based component on the surface of the resin particle.
[0087] Resin particles having a surface absorbance ratio S within the specific range and a ratio S / I of the surface absorbance ratio S to the internal absorbance ratio I within the specific range can increase the yield of hollow particles having desired structures and properties. From the same viewpoint, the lower limit of the ratio S / I of the surface absorbance ratio S to the internal absorbance ratio I is preferably 0.4, more preferably 0.5, and even more preferably 0.6. The upper limit of the ratio S / I is preferably 2, and more preferably 1.
[0088] The method for calculating the internal absorbance ratio I described above is similar to the method for calculating the surface absorbance ratio S, except that the resin particle is divided into roughly two equal parts, and then a diamond prism is placed against the split surface exposed by the division of one of the two hemispherical particles obtained by the division.
[0089] (Method of manufacturing hollow particles) As a method for producing the hollow particles, for example, a method can be adopted in which resin particles containing an organic physical foaming agent and the composite resin as a base resin are prepared, and then the resin particles are foamed.
[0090] As a method for producing resin particles, for example, a method can be adopted in which a styrene-based resin core particle (hereinafter referred to as "core particle" as appropriate) having a styrene-based resin as a base resin is impregnated with a (meth)acrylic acid ester monomer and a styrene-based monomer, the (meth)acrylic acid ester monomer and the styrene-based monomer are polymerized, and the particle is impregnated with a physical foaming agent.
[0091] More specifically, the method for producing resin particles includes a dispersing step of dispersing core particles in an aqueous medium, a modification step of impregnating the core particles dispersed in the aqueous medium with a (meth)acrylic acid ester monomer and a styrene-based monomer, and polymerizing the (meth)acrylic acid ester monomer and the styrene-based monomer to obtain resin particles; and an impregnation step of impregnating the core particles or the resin particles with an organic physical foaming agent at least once or more times among before, during, and after the modification step. The dispersion step, the modification step, and the impregnation step may be performed consecutively in a single sealed container, or may be performed using separate containers. Each step will be described in detail below.
[0092] [Dispersion process] In the dispersion step, the core particles are dispersed in an aqueous medium to prepare a suspension. As the aqueous medium, for example, deionized water or the like can be used. In addition to the core particles, a suspending agent, a surfactant, or the like can be added to the aqueous medium as necessary.
[0093] The base resin of the core particles used in the dispersion step is preferably a styrene-based resin. As the styrene-based resin, the above-mentioned homopolymer of the styrene-based monomer, or a copolymer of the styrene-based monomer with another monomer or polymer, etc. can be used. More specifically, as the styrene-based resin, for example, a homopolymer of a styrene-based monomer such as polystyrene, or a copolymer containing 50 mol% or more of a component derived from a styrene-based monomer, etc. can be used. In addition, the core particles may contain additives such as a bubble adjuster, a pigment, a slip agent, an antistatic agent, and a flame retardant, within a range that does not impair the above-mentioned action and effect.
[0094] The core particle may contain other resins than the styrene resin, such as an acrylic resin that is a polymer of a (meth)acrylic acid ester monomer. From the viewpoint of more reliably making the hollow particle have a desired structure, the content of the other resins than the styrene resin in the core particle is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the styrene resin.
[0095] The method for producing the core particles is not particularly limited. For example, the strand cut method, the underwater cut method, the hot cut method, etc. can be used as the method for producing the core particles. In addition, the core particles may be produced by, for example, a suspension polymerization method in which a styrene-based monomer or the like is polymerized in an aqueous medium.
[0096] The average particle diameter of the core particles is preferably 0.6 mm or more and 2.0 mm or less, and more preferably 0.7 mm or more and 1.5 mm or less. In this case, the polymerization stability in the modification process is improved, and the weight average molecular weight of the composite resin is easily increased. In addition, by performing the modification process and the impregnation process using core particles whose average particle diameter is within the specific range, the average particle diameter of the resin particles and the surface absorbance ratio S of the resin particles can be easily adjusted to the specific range, and the structure of the hollow particles finally obtained can be more reliably made to be the desired structure.
[0097] The average particle diameter of the core particles is the cumulative 63% diameter (i.e., d63) value calculated based on the particle size distribution on a volume basis of the core particles, and can be measured using a particle size distribution measuring device (for example, "Militrack JPA" manufactured by Nikkiso Co., Ltd.).
[0098] Examples of the suspending agent used in the dispersion step include inorganic suspending agents consisting of inorganic particles such as tricalcium phosphate, hydroxyapatite, magnesium pyrophosphate, magnesium phosphate, aluminum hydroxide, ferric hydroxide, titanium hydroxide, magnesium hydroxide, barium phosphate, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, barium sulfate, talc, kaolin, and bentonite, and organic suspending agents such as polyvinylpyrrolidone, polyvinyl alcohol, ethyl cellulose, and hydroxypropylmethylcellulose. These suspending agents may be used alone or in combination of two or more. The suspending agent is preferably one or more of tricalcium phosphate, hydroxyapatite, and magnesium pyrophosphate.
[0099] The amount of the suspending agent added is preferably 0.05 parts by mass or more and 10 parts by mass or less, more preferably 0.3 parts by mass or more and 5 parts by mass or less, based on 100 parts by mass of the aqueous medium, in terms of solid content. By making the amount of the suspending agent added 0.05 parts by mass or more, more preferably 0.3 parts by mass or more, when the (meth)acrylic acid ester monomer and the styrene-based monomer are added in the subsequent modification step, the state in which the core particles and the monomers are suspended in the aqueous medium is more easily maintained. In addition, by making the amount of the suspending agent added 10 parts by mass or less, more preferably 5 parts by mass or less, the particle size distribution of the hollow particles finally obtained can be narrowed.
[0100] Examples of the surfactant that can be used include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. Examples of the anionic surfactants include sodium alkylsulfonate, sodium alkylbenzenesulfonate, sodium lauryl sulfate, sodium α-olefinsulfonate, and sodium dodecylphenylether disulfonate. Examples of the nonionic surfactants include polyoxyethylene dodecyl ether, polyoxyethylene nonylphenyl ether, and polyoxyethylene lauryl ether.
[0101] Examples of cationic surfactants include alkylamine salts such as coconut amine acetate and stearyl amine acetate, and quaternary ammonium salts such as lauryl trimethyl ammonium chloride and stearyl trimethyl ammonium chloride. Examples of amphoteric surfactants include alkyl betaines such as lauryl betaine and stearyl betaine, and alkyl amine oxides such as lauryl dimethyl amine oxide. These surfactants may be used alone or in combination of two or more.
[0102] The surfactant is preferably an anionic surfactant, more preferably an alkali metal alkylsulfonate having from 8 to 20 carbon atoms, and even more preferably sodium alkylsulfonate having from 8 to 20 carbon atoms. By using these surfactants, the core particles, monomers, etc. can be more easily maintained in a suspended state in the aqueous medium when the (meth)acrylic acid ester monomer and the styrene monomer are added in the subsequent modification step.
[0103] If necessary, an electrolyte consisting of an inorganic salt such as lithium chloride, potassium chloride, sodium chloride, sodium sulfate, sodium nitrate, sodium carbonate, or sodium bicarbonate may be added to the suspension.
[0104] [Modification process] In the modification step, a (meth)acrylic acid ester monomer and a styrene-based monomer are added to the suspension, and the core particles are impregnated with the (meth)acrylic acid ester monomer and the styrene-based monomer, and these monomers are polymerized. This produces composite resin particles having a composite resin containing a styrene-based component and a (meth)acrylic acid ester component as a base resin.
[0105] The total amount of the (meth)acrylic acid ester monomer and the styrene-based monomer added in the modification step is, for example, preferably 200 parts by mass or more and 700 parts by mass or less, more preferably 250 parts by mass or more and 600 parts by mass or less, relative to 100 parts by mass of the core particles. The ratio of the amount of the (meth)acrylic acid ester monomer and the amount of the styrene-based monomer to be added may be appropriately set according to the composition of the desired composite resin. From the viewpoint of easily obtaining good hollow particles, the ratio of the amount of the (meth)acrylic acid ester monomer and the amount of the styrene-based monomer to be added is preferably (meth)acrylic acid ester monomer:styrene monomer=50:50 to 85:15, more preferably (meth)acrylic acid ester monomer:styrene monomer=60:40 to 75:25, in terms of mass ratio.
[0106] In the modification step, a polymerization initiator is used to polymerize the (meth)acrylic acid ester monomer and the styrene-based monomer. The polymerization initiator is not particularly limited as long as it is applicable to the suspension polymerization of the styrene-based monomer. For example, a polymerization initiator that is soluble in a vinyl monomer and has a 10-hour half-life temperature of 50°C or more and 120°C or less can be used. Examples of such polymerization initiators include organic peroxides such as cumene hydroxyperoxide, dicumyl peroxide, t-butylperoxy-2-ethylhexanoate, t-butylperoxybenzoate, benzoyl peroxide, t-butylperoxyisopropyl carbonate, t-amylperoxy-2-ethylhexyl carbonate, hexylperoxy-2-ethylhexyl carbonate, and lauroyl peroxide, and azo compounds such as azobisisobutyronitrile. These polymerization initiators may be used alone or in combination of two or more.
[0107] The polymerization initiator may be added to an aqueous medium in a state dissolved in a solvent or monomer, and impregnated into the core particles together with the (meth)acrylic acid ester monomer and the styrene-based monomer. In this case, the solvent may be, for example, an aromatic hydrocarbon such as ethylbenzene or toluene, or an aliphatic hydrocarbon such as heptane or octane. The amount of the polymerization initiator added is preferably 0.01 parts by mass or more and 3 parts by mass or less with respect to 100 parts by mass of the total of the (meth)acrylic acid ester monomer and the styrene-based monomer added in the modification step.
[0108] In the modification step, a cell regulator, a plasticizer, an oil-soluble polymerization inhibitor, a flame retardant, a dye, etc. can be added as necessary. The cell regulator is added to the aqueous medium in a state where it is dissolved or dispersed in a monomer and / or a solvent. Examples of the cell regulator include fatty acid monoamide, fatty acid bisamide, talc, silica, polyethylene wax, methylene bisstearic acid, methyl methacrylate copolymer, and silicone. Examples of the fatty acid monoamide include oleic acid amide and stearic acid amide. Examples of the fatty acid bisamide include ethylene bisstearic acid amide.
[0109] The plasticizer, oil-soluble polymerization inhibitor, flame retardant, and dye can be added to the aqueous medium in a state where they are dissolved or dispersed in, for example, a (meth)acrylic acid ester monomer and / or a styrene monomer. Examples of the plasticizer include fatty acid esters such as glycerin tristearate, glycerin trioctoate, glycerin trilaurate, sorbitan tristearate, sorbitan monostearate, and butyl stearate, acetylated monoglycerides such as glycerin diacetomonolaurate, oils and fats such as hardened beef tallow and hardened castor oil, and organic compounds such as cyclohexane and liquid paraffin. Examples of the oil-soluble polymerization inhibitor include para-t-butylcatechol, hydroquinone, and benzoquinone.
[0110] The heating temperature in the modification process and the time required for adding the (meth)acrylic acid ester monomer and the styrene-based monomer may be appropriately set depending on the chemical structure of the styrene-based resin of the core particles, the chemical structures of the (meth)acrylic acid ester monomer and the styrene-based monomer, the characteristics of the polymerization initiator, the desired degree of polymerization of the composite resin, etc.
[0111] The composite resin particles obtained after the modification step preferably have a structure in which the surface layer of the resin particles contains a large amount of (meth)acrylic acid ester components, while the interior of the resin particles contains a large amount of styrene-based components. In the foaming step, by foaming the resin particles in which the (meth)acrylic acid ester components and the styrene-based components are distributed as described above, foaming inside the resin particles is promoted and the progress of foaming on the surface layer of the resin particles is suppressed, thereby further increasing the yield of hollow particles having an outer shell layer and a hollow portion.
[0112] [Impregnation process] In the impregnation step, the core particles or composite resin particles are impregnated with the organic physical foaming agent at least once among the timings before the modification step, during the modification step, and after the completion of the modification step, to obtain resin particles. That is, the impregnation step may be performed on the core particles before the (meth)acrylic acid ester monomer and the styrene-based monomer are impregnated, or on the composite resin particles in the middle of polymerization of the (meth)acrylic acid ester monomer and the styrene-based monomer in the modification step, or on the composite resin particles after the polymerization of the (meth)acrylic acid ester monomer and the styrene-based monomer is completed. In addition, the core particles or composite resin particles may be impregnated with the organic physical foaming agent at two or more of these timings. From the viewpoint of sufficiently impregnating the organic physical foaming agent into the inside of the composite resin particles and facilitating the hollow particle to have a desired structure, it is preferable to perform the impregnation step at least before the modification step. From the same viewpoint, it is more preferable that the impregnation step is carried out before the modification step, and at least one of during the modification step and after the completion of the modification step. When the impregnation step is carried out multiple times, the organic physical foaming agent used in each impregnation step may be the same or different from each other.
[0113] When impregnating the core particles or composite resin particles with the organic physical foaming agent, for example, the organic physical foaming agent may be supplied into a sealed container in which these particles are housed to increase the pressure inside the sealed container. By maintaining this state, the organic physical foaming agent can be impregnated into the core particles or composite resin particles.
[0114] During the impregnation of the core particles or composite resin particles with the organic physical foaming agent, the inside of the closed container may be heated as necessary. Heating the inside of the closed container can further promote the impregnation of the core particles or composite resin particles with the organic physical foaming agent. The temperature and time for impregnating the organic physical foaming agent may be appropriately set according to the timing of the impregnation process. For example, in the impregnation process performed before the modification process, it is preferable to impregnate the core particles with the organic physical foaming agent by maintaining a temperature of about 40°C to 90°C for 0.5 hours to 3 hours. In the impregnation process performed during and / or after the completion of the modification process, it is preferable to impregnate the core particles or composite resin particles with the organic physical foaming agent by maintaining a temperature of about 80°C to 120°C for 3 hours to 5 hours.
[0115] The amount of the organic physical foaming agent in the impregnation step is, for example, preferably 1 part by mass or more and 10 parts by mass or less, more preferably 3 parts by mass or more and 9 parts by mass or less, and even more preferably 5 parts by mass or more and 8 parts by mass or less, per 100 parts by mass of the composite resin particles.
[0116] As described above, the impregnation step can be performed to obtain resin particles containing an organic physical foaming agent. After the impregnation step, the obtained resin particles may be dehydrated and dried as necessary. The method of dehydration and drying is not particularly limited, but for example, a method of dehydrating and drying the resin particles by blowing hot air onto the resin particles using an airflow dryer can be adopted. By dehydrating and drying the resin particles, the amount of water contained in the resin particles can be reduced, and the excess organic physical foaming agent contained in the surface layer of the resin particles can be easily dispersed while maintaining the expandability of the resin particles. This makes it easier to form a good outer shell layer on the hollow particles, even if the hollow particles have a low apparent density. When using an airflow dryer, for example, the hot air temperature can be appropriately set within a range of 30°C to 60°C, and the drying time can be appropriately set within a range of 0.5 hours to 4 hours.
[0117] The average particle diameter of the resin particles is 1.0 mm or more and 5.0 mm or less. When the resin particles have an average particle diameter in the specific range and a surface absorbance ratio S in the specific range, the structure of the hollow particles finally obtained can be made more reliably the desired structure. From the viewpoint of further increasing the yield of hollow particles having the specific structure, the average particle diameter of the resin particles is preferably 1.1 mm or more and 4.0 mm or less, and more preferably 1.2 mm or more and 3.0 mm or less.
[0118] The average particle diameter of the resin particles is the cumulative 63% diameter (i.e., d63) calculated based on the particle size distribution of the resin particles on a volume basis, and can be measured using a particle size distribution measuring device (for example, "Militrack JPA" manufactured by Nikkiso Co., Ltd.).
[0119] From the viewpoint of easily forming a good outer shell layer on hollow particles even in the case of hollow particles with a low apparent density, the moisture content of the resin particles is preferably 0.01% by mass or more and 1% by mass or less, more preferably 0.03% by mass or more and 0.5% by mass or less, and even more preferably 0.05% by mass or more and 0.4% by mass or less. After the impregnation step, a coating step may be carried out, if necessary, to coat the surfaces of the resin particles with a surface coating agent.
[0120] Examples of the surface coating agent used in the coating process include zinc stearate, stearate triglyceride, stearate monoglyceride, and hardened castor oil. Antistatic agents can also be used as the surface coating agent in the coating process. The amount of the surface coating agent added is preferably 0.01 to 2 parts by mass per 100 parts by mass of the resin particles.
[0121] Hollow particles can be obtained by expanding resin particles containing an organic physical foaming agent. For example, a method of heating resin particles with a heating medium can be adopted as a method of expanding resin particles. Specifically, the resin particles can be expanded by introducing a heating medium such as steam into a pre-expander to which resin particles containing an organic physical foaming agent are supplied.
[0122] When expanding resin particles containing an organic physical blowing agent, the resin particles may be expanded in one stage or in multiple stages. In the latter case, for example, the resin particles may be expanded to produce first-stage hollow particles having an apparent density higher than the target apparent density, and the first-stage hollow particles may be further expanded to produce hollow particles having the desired apparent density. EXAMPLES
[0123] Specific embodiments of the impact absorbing material and the manufacturing method thereof will be described below. Note that the specific embodiments of the impact absorbing material according to the present invention are not limited to the embodiments of Examples 1 to 4 described below, and the configurations can be appropriately changed within the scope of the present invention.
[0124] Example 1 The impact absorbing material 1 of this example is produced by molding hollow particles 2 having an outer shell layer 21 and a hollow portion 22 surrounded by the outer shell layer 21 in a mold, as shown in FIG. 1. The outer shell layer 21 of the hollow particle 2 has a resin film 211 whose base resin is a composite resin containing a (meth)acrylic acid ester component and a styrene-based component. In addition, as shown in FIG. 1 and FIG. 2, the impact absorbing material 1 has a fused portion 11 formed by fusing the outer shell layers 21 of the hollow particles 2 to each other. The apparent density of the impact absorbing material 1, the average particle diameter of the hollow particles 2 in the impact absorbing material 1, and the average value of the total thickness of the resin film 211 in the fused portion 11 are as shown in Table 1.
[0125] In producing the impact absorbing material 1 of this example, first, core particles containing a styrene-based resin were produced by a suspension polymerization method, and then resin particles containing an organic physical foaming agent were produced using these core particles. Hollow particles were obtained by expanding these resin particles. The hollow particles thus obtained were molded in a mold to obtain the impact absorbing material 1. The method for producing the impact absorbing material 1 will be described in detail below.
[0126] [Creation of core particles] First, 765 g of deionized water, 0.84 g of a suspending agent, and 3.2 g of a surfactant were placed in a 3 L autoclave equipped with a stirrer. The suspending agent used was tribasic calcium phosphate (manufactured by Taihei Chemical Industry Co., Ltd.), and the surfactant used was sodium dodecylbenzenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0127] Next, while stirring the contents of the autoclave, a polymerization initiator, a plasticizer, and 848 g of styrene were put into the autoclave. As the polymerization initiator, 2.2 g of t-butylperoxy 2-ethylhexanoate ("Perbutyl (registered trademark) O" manufactured by NOF Corporation) and 0.44 g of t-butylperoxy 2-ethylhexyl monocarbonate ("Perbutyl (registered trademark) E" manufactured by NOF Corporation) were used in combination. As the plasticizer, 12.7 g of cyclohexane and 6.2 g of hardened beef tallow were used in combination. The plasticizer was dissolved in styrene and put into the autoclave.
[0128] The contents of the autoclave were stirred at room temperature for 30 minutes, and the temperature inside the autoclave was then raised to 90°C over 1.5 hours. After the temperature inside the autoclave reached 90°C, the autoclave was further heated, and the temperature inside the autoclave was raised to 100°C over 5.5 hours. After the temperature inside the autoclave reached 100°C, the autoclave was further heated, and the temperature inside the autoclave was raised to 110°C over 1.5 hours. This temperature was maintained for 2 hours, and then the autoclave was cooled to 30°C over 4 hours. Through the above operations, core particles using polystyrene as the base resin were produced.
[0129] After cooling was completed, the core particles were removed from the autoclave, and tricalcium phosphate adhering to the surface of the core particles was removed using nitric acid. The core particles were dehydrated and washed using a centrifuge, and then moisture adhering to the surface of the core particles was removed using an airflow dryer. The average particle size of the core particles obtained by the above is as shown in Table 1. The average particle size of the core particles is the cumulative 63% diameter (i.e., d63) value in the volume-based particle size distribution obtained using a particle size distribution measuring device ("Millitrack JPA" manufactured by Nikkiso Co., Ltd.).
[0130] [Preparation of resin particles containing organic physical foaming agents] 965 g of deionized water and 6.0 g of sodium pyrophosphate were placed in a 3 L autoclave equipped with a stirrer. Then, 12.9 g of powdered magnesium nitrate hexahydrate was placed in the autoclave, and the contents of the autoclave were stirred at 40° C. for 30 minutes. As a result, the contents of the autoclave were converted into a slurry of magnesium pyrophosphate as a suspending agent.
[0131] Next, the surfactant, 200 g of core particles, and a polymerization initiator were charged into the autoclave. As the surfactant, a 1% by mass aqueous solution of sodium lauryl sulfonate was used, and the amount of the surfactant added was 0.04 g as sodium lauryl sulfonate. As the polymerization initiator, 2.4 g of benzoyl peroxide (NOF Corp.'s "Niper (registered trademark) BW") was used.
[0132] After replacing the atmosphere in the autoclave with nitrogen, 18 g of an organic physical blowing agent, a mixture of about 70% by mass of normal butane and about 30% by mass of isobutane, was added to the autoclave over a period of 10 minutes.
[0133] After the addition of the organic physical foaming agent, the temperature inside the autoclave was kept at 40°C for 1 hour. The temperature inside the autoclave was then raised to 80°C over 1 hour. While maintaining this temperature, a mixture of 200g of styrene, 400g of methyl methacrylate, and a polymerization initiator was added to the autoclave over 6 hours while stirring the inside of the autoclave at a stirring speed of 450 rpm. As the polymerization initiator, 1.2g of t-butyl peroxybenzoate ("Perbutyl Z" manufactured by NOF Corporation) was used.
[0134] Thirty minutes after the addition of styrene and methyl methacrylate, 80 g of pentane as an organic physical foaming agent was added to the autoclave over 30 minutes. Also, 30 minutes after the addition of styrene and methyl methacrylate, the temperature inside the autoclave was raised to 110°C over 1.5 hours and maintained at this temperature for 4 hours. The inside of the autoclave was then cooled to 35°C over about 6 hours. Through the above operations, a composite resin containing a component derived from styrene and a component derived from methyl methacrylate was used as the base resin, and resin particles containing an organic physical foaming agent were produced.
[0135] After cooling was completed, the resin particles were removed from the autoclave, and the tricalcium phosphate adhering to the surface of the resin particles was removed using nitric acid. The resin particles were dehydrated and washed using a centrifuge, and then the moisture adhering to the surface of the resin particles was removed using an airflow dryer. The average particle size of the resin particles obtained by the above, the weight average molecular weight of the composite resin, the moisture content in the resin particles, and the content of the organic physical foaming agent in the resin particles were as shown in Table 1. The average particle size of the resin particles is the cumulative 63% diameter (i.e., d63) value in the volume-based particle size distribution obtained using a particle size distribution measuring device ("Militrack JPA" manufactured by Nikkiso Co., Ltd.).
[0136] In this example, the surfaces of the resin particles obtained as described above were coated with a surface coating agent. Specifically, a mixture of 0.11 parts by mass of zinc stearate, 0.053 parts by mass of glycerin monostearate, 0.004 parts by mass of talc, and 0.065 parts by mass of an antistatic agent ("Resistat (registered trademark) PE132" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added to 100 parts by mass of the resin particles, and the surfaces of the resin particles were coated with the surface coating agent containing these.
[0137] In addition, after the surface of the resin particles was coated with a surface coating agent, the resin particles were further subjected to a drying treatment in which the resin particles were heated at a temperature of 40°C for 1 hour using an airflow dryer to remove excess moisture and the organic physical blowing agent.
[0138] [Preparation of hollow particles] The resin particles obtained by the above-mentioned method were put into a normal pressure batch expansion machine with a volume of 30 L, and steam was supplied into the expansion machine. The temperature of the steam was 120°C, and the heating time was 90 seconds. In this way, the resin particles were expanded, and hollow particles having the bulk density shown in Table 1 were obtained.
[0139] [Making shock absorbing materials] The hollow particles were molded in a mold using a molded product molding machine (Tabo Seimitsu Co., Ltd., "DSM-0705VS"). First, the hollow particles obtained as described above were aged for one day in a thermostatic chamber at a temperature of 23°C. Next, the hollow particles were filled into a mold having a rectangular parallelepiped molding cavity of 300 mm x 75 mm x 25 mm equipped in the molding machine. Steam with a gauge pressure of 0.07 MPa (G) was introduced into this mold to heat the hollow particles, thereby performing in-mold molding. The obtained molded body was dried in a drying chamber at a temperature of 40°C for one day, and then further aged in a thermostatic chamber at a temperature of 23°C for one day. In this way, an apparent density of 25 kg / m 3 The impact absorbing material was obtained by measuring the ratio of particles other than the hollow particles in the impact absorbing material by the above-mentioned method. In this example, the impact absorbing material did not contain any particles other than the hollow particles.
[0140] Example 2 The manufacturing method of the impact absorbing material of Example 2 is the same as that of Example 1, except that after the surfaces of the resin particles containing an organic physical foaming agent are coated with a surface coating agent, drying with an air flow dryer is not performed before foaming, and the foaming conditions are changed so that the bulk density of the hollow particles becomes the value shown in Table 1.
[0141] Example 3 The manufacturing method of the impact absorbing material of Example 3 was the same as that of Example 1, except that the foaming conditions were changed so that the bulk density of the hollow particles would have the values shown in Table 1.
[0142] (Example 4 and Comparative Examples 1 to 2) The manufacturing methods of the impact absorbing materials of Example 4 and Comparative Example 1-2 are the same as those of Example 1, except that the polymerization conditions were changed so that the average particle diameters of the core particles and resin particles were the values shown in Table 1, that after the surfaces of the resin particles containing an organic physical foaming agent were coated with a surface coating agent, drying with an airflow dryer was not performed before foaming, and that the foaming conditions were changed so that the bulk density of the hollow particles was the value shown in Table 1.
[0143] (Reference example) The impact absorbing material of the Reference Example is produced by molding expanded polystyrene resin particles in a mold. The expanded polystyrene resin particles used in producing the impact absorbing material of the Reference Example are produced by expanding polystyrene resin particles having an average particle diameter shown in Table 1. The bulk density of the expanded polystyrene resin particles used in producing the impact absorbing material of the Reference Example is as shown in Table 1. The impact absorbing material of the Reference Example is produced by molding such expanded polystyrene resin particles in a mold under the same conditions as in Example 1.
[0144] Next, methods for evaluating the various properties of the resin particles, hollow particles, and impact absorbing materials obtained as above will be described below.
[0145] [Surface absorbance ratio S and internal absorbance ratio I of resin particles] Using a Fourier transform infrared spectrophotometer ("FT / IR-460plus" manufactured by JASCO Corporation) and a total reflection absorption measuring device ("ATR PRO450-S" manufactured by JASCO Corporation), the infrared absorption spectrum of the surface and the infrared absorption spectrum of the internal of the resin particles were obtained by the above-mentioned method. Then, based on these infrared absorption spectra, the surface absorbance ratio S, the internal absorbance ratio I, and the ratio S / I of the surface absorbance ratio S to the internal absorbance ratio I were calculated. These values for the resin particles of the Examples, Comparative Examples, and Reference Examples were as shown in Table 1.
[0146] [Weight average molecular weight of base resin] A chromatogram of the hollow particles was obtained by gel permeation chromatography (GPC) using polystyrene as a standard substance, and the weight average molecular weight calculated from the obtained chromatogram was regarded as the weight average molecular weight of the base resin.
[0147] Specifically, HLC-8320GPC EcoSEC manufactured by Tosoh Corporation was used to obtain the chromatogram. After preparing a sample solution with a concentration of 0.1 wt% by dissolving resin particles as a measurement sample in tetrahydrofuran (THF), the measurement sample was separated by gel permeation chromatography (GPC) according to the difference in molecular size using a column consisting of one TSKguardcolumn SuperH-H and two TSK-GEL SuperHM-H connected in series under the following separation conditions: eluent: tetrahydrofuran (THF) and THF flow rate: 0.6 ml / min, to obtain a chromatogram. Then, the retention time in the chromatogram was converted into molecular weight using a calibration curve created using standard polystyrene, to obtain a differential molecular weight distribution curve. The weight average molecular weight of the base resin was calculated from this differential molecular weight distribution curve. The column "Weight average molecular weight of base resin" in Table 1 shows the weight average molecular weight of the composite resin in the examples and comparative examples, and the weight average molecular weight of the styrene-based resin in the reference example.
[0148] [Water content in resin particles] Approximately 0.3 g of resin particles was heated to a temperature of 160° C. using a thermal moisture vaporizer to vaporize the moisture in the resin particles. The vaporized moisture was introduced into a Karl Fischer moisture analyzer ("AQ-6" manufactured by Hiranuma Sangyo Co., Ltd.) connected to the thermal moisture vaporizer to measure the moisture content in the resin particles.
[0149] [Content of organic physical foaming agent in resin particles] Approximately 1 g of resin particles, accurately weighed to four decimal places, was dried for four hours in a hot air dryer set at 120°C. The dried resin particles were cooled to room temperature, and then the mass of the dried resin particles was accurately measured to four decimal places. The total volatile content was calculated from the change in mass before and after heating according to the following formula. Total volatile content (unit: mass%) = {mass before heating (unit: g) - mass after heating (unit: g)} ÷ mass before heating (unit: g) × 100
[0150] The content of the organic physical foaming agent in the resin particles was determined by subtracting the water content (unit: mass %) from the total volatile content.
[0151] [Hollow particle structure] After dividing the hollow particle into roughly two equal parts, the cut surface of the hollow particle was observed using an electron microscope. As an example, the cut surface of hollow particle 2 in Example 1 is shown in Figures 3 and 4. As shown in Figures 3 and 4, hollow particle 2 in Example 1 has an outer shell layer 21 provided with a resin film 211 and a hollow portion 22 surrounded by the outer shell layer 21.
[0152] The hollow portion 22 of the hollow particle 2 is a single space separated from the external space of the hollow particle 2 by an outer shell layer 21, as shown in Fig. 3, for example. Although the hollow portion 22 of the hollow particle 2 shown in Fig. 3 is composed of a single space, the hollow portion 22 may be partitioned into several to several tens of spaces by space walls. As shown in Fig. 4, a plurality of air bubbles 212 partitioned by a resin film 211 are formed in the outer shell layer 21 of the hollow particle 2.
[0153] Like the hollow particles of Example 1, the hollow particles of Examples 2 to 4 and Comparative Examples 1 and 2 also have an outer shell layer and a hollow portion surrounded by the outer shell layer.
[0154] On the other hand, as shown in FIG. 5, in the expanded beads 8 of the reference example, air bubbles are formed relatively uniformly throughout the inside of the beads, and no hollow portions exist.
[0155] [Bulk density of hollow particles and expanded particles] 1.5 g of hollow particles or expanded particles were left for 10 days under conditions of 50% relative humidity, 23°C temperature, and 1 atm to adjust the condition. A measuring cylinder with a volume of 200 mL was prepared, and the particles after the adjustment were placed in the measuring cylinder and allowed to accumulate naturally. After that, a light impact was applied to the bottom of the measuring cylinder to stabilize the filling height of the particles in the measuring cylinder. The bulk volume of the particles (unit: L) indicated by the graduations on the measuring cylinder was then read. The bulk density (unit: kg / m) of the hollow particles or expanded particles was calculated by dividing the mass of the particles placed in the measuring cylinder by the bulk volume and converting the unit. 3 The bulk density of the hollow particles or expanded particles of the Examples and Comparative Examples is shown in Table 1.
[0156] [Average thickness of the outer shell layer of hollow particles before molding] The method for calculating the average thickness of the outer shell layer of the hollow particles before molding in the mold is as described above. The average thicknesses of the outer shell layers of the hollow particles of the Examples and Comparative Examples are as shown in Table 1.
[0157] In measuring the thickness of the outer shell layer, there may be a giant bubble with a length of 100 μm or more in the thickness direction of the outer shell layer near the inner surface of the outer shell layer. In this example, such a bubble was treated as a hollow part. Specifically, when the giant bubble described above is present near the inner surface of the outer shell layer, the length of the line segment from the outer surface of the hollow particle to the bubble described above was taken as the thickness of the outer shell layer.
[0158] In addition, the expanded beads of the reference example have uniform bubbles formed over the entire cut surface, so the thickness of the outer shell layer cannot be measured. Therefore, the symbol "-" is entered in the "Average thickness of the outer shell layer" column of the reference example. The thickness of the resin film on the outermost surface of the expanded beads of the reference example is about 2 μm.
[0159] [Average total thickness of resin film in the outer shell layer of hollow particles before molding] The method for calculating the average value of the total thickness of the resin film in the outer shell layer of the hollow particles before molding in the mold is as described above. The average values of the total thickness of the resin film in the hollow particles of the Examples and Comparative Examples are as shown in Table 1. In addition, the "Resin film / outer shell layer" column in Table 1 lists the value obtained by dividing the average value of the total thickness of the resin film by the average thickness of the outer shell layer.
[0160] [Apparent density ρ of shock absorbing material] The mass (unit: kg) of the shock absorbing material is calculated based on the external dimensions and the volume (unit: m 3 ) is the apparent density ρ (unit: kg / m 3 The apparent density ρ of the impact absorbing materials of the Examples, Comparative Examples and Reference Examples is as shown in Table 2.
[0161] [Average particle size D of hollow or expanded particles in impact absorbing material] The impact absorbing material was cut in the center of its length along the thickness direction of the impact absorbing material to expose the cut surface. Next, a photograph of the cut surface of the molded body was taken, and five lines along the thickness direction of the impact absorbing material were drawn randomly on the obtained photograph from one edge to the opposite edge of the photograph. Next, the number of particles intersecting with the lines was counted. Then, the total length of each line was divided by the total number of particles intersecting with each line to calculate the average particle diameter D (unit: mm) of the hollow particles or expanded particles in the impact absorbing material. The average particle diameter D of the hollow particles in the impact absorbing materials of the examples and comparative examples, and the average particle diameter D of the expanded particles in the impact absorbing material of the reference example were as shown in Table 2. Note that the impact absorbing materials of the examples and comparative examples did not contain any particles other than the hollow particles.
[0162] [Average total thickness of resin film in fusion zone t r ] The impact absorbing material was cut in the center of its longitudinal direction to expose the cut surface. Using a scanning electron microscope, 30 fusion parts to be observed were randomly selected from the multiple fusion parts that appeared on the cut surface. Each fusion part to be observed was observed at a magnification of 200 times to obtain an enlarged photograph of each fusion part. Next, a line segment extending in the thickness direction of the fusion part was drawn on the fusion part in each enlarged photograph from one surface of the fusion part to the other surface of the fusion part.
[0163] The above operations were carried out at 10 positions randomly selected from each enlarged photograph, the length of the line segments extending in the thickness direction of the fused portion was measured, and the length of each line segment that overlapped with an air bubble was calculated. Next, the length of the portion that overlapped with an air bubble was subtracted from the length of each line segment, and these values were arithmetically averaged to calculate the total thickness of the resin film at each fused portion. The total thickness of the resin film described above was then calculated for 30 randomly selected fused portions, and the arithmetic average value of these total thicknesses of the resin film was calculated, which was called the average total thickness t of the resin film at the fused portions. r (Unit: μm) The average total thickness t of the resin film in the fusion portion of the impact absorbing material in the examples and the comparative examples r The results were as shown in Table 2.
[0164] [Average thickness of fusion part t t ] The average total thickness of the resin film in the fusion zone mentioned above, t r The average thickness t of the fused portion exposed on the cut surface is calculated by arithmetically averaging the lengths of the line segments extending in the thickness direction of the fused portion measured in the measurement of t The average thickness t of the fused portion in the impact absorbing materials of the examples and the comparative examples was calculated (unit: μm). t The results were as shown in Table 2.
[0165] [Compression characteristics] A rectangular specimen measuring 50 mm in length, 50 mm in width, and 25 mm in thickness was taken from the center of the impact absorbing material. A compression test was conducted on the specimen based on the method specified in JIS K7220:2006, and a stress-strain curve was obtained. The compression test was conducted in a laboratory at 23°C.
[0166] 10% deformation compressive stress σ in the examples, comparative examples and reference examples calculated based on the stress-strain curve 10 (Unit: kPa), 25% deformation compressive stress σ 25 (Unit: kPa), 50% deformation compressive stress σ 50 (Unit: kPa) and 75% deformation compressive stress σ 75 (Unit: kPa) is as shown in Table 2. 25 / σ 50 The column shows the 50% deformation compressive stress σ 50 25% deformation compressive stress σ 25 The ratio of these two values expressed as a percentage is called "σ 75 / σ 50 The column shows the 50% deformation compressive stress σ 50 75% deformation compressive stress σ 75 The ratio of these two values expressed as a percentage is called "σ 10 / σ 75 The column shows the 75% deformation compressive stress σ 75 10% deformation compressive stress σ 10 The ratios are shown as percentages.
[0167] [Energy absorption characteristics] The energy absorption efficiency (unit: %) at a certain strain amount ε1 (unit: %) is a value calculated by the following method based on the stress-strain curve obtained by the above-mentioned method. First, as shown in FIG. 6, the area S1 of the region on the stress-strain curve surrounded by the portion L1 from point P0 where the strain amount is 0% to point P1 where the strain amount is ε1, the horizontal axis, and a straight line L2 that passes through point P1 and is parallel to the vertical axis is calculated. Separately, the area S0 of the rectangular region on the stress-strain curve surrounded by a straight line L3 that passes through point P1 and is parallel to the horizontal axis, a straight line L2 that passes through point P1 and is parallel to the vertical axis, the vertical axis, and the horizontal axis is calculated. Then, the ratio S1 / S0 of the area S1 to the area S0 expressed as a percentage is defined as the energy absorption efficiency (unit: %) at the strain amount ε1.
[0168] Table 2 shows the energy absorption efficiency at a strain of 25%, the energy absorption efficiency at a strain of 50%, and the energy absorption efficiency at a strain of 75% in the examples, comparative examples, and reference examples.
[0169] In addition, the area enclosed by the horizontal axis and the straight line passing through the part of the stress-strain curve from 0% strain to 50% strain measured by the compression test and the point of 50% strain on the stress-strain curve, parallel to the vertical axis, was calculated, and this value was taken as the energy absorption amount up to 50% strain. The energy absorption amount per volume was calculated by dividing this energy absorption amount by the volume of the impact absorbing material used in the test. The energy absorption amount per mass was also calculated by dividing the energy absorption amount per volume by the apparent density of the impact absorbing material used in the test. These values were as shown in Table 2.
[0170] The aforementioned energy absorption amount per mass is preferably 5 J / g or more, and more preferably 6 J / g. In this case, the component weight of the impact absorbing material can be made lighter while maintaining good energy absorption performance. The aforementioned energy absorption amount per mass is preferably 10 J / g or less, and more preferably 8 J / g or less. In this case, the impact absorbing material does not become too hard, and can absorb impact appropriately, and when used as an automobile material, it becomes easier to ensure the safety of passengers in the event of a collision.
[0171] [Compression set] A rectangular parallelepiped test piece measuring 50 mm in length, 50 mm in width and 25 mm in thickness was taken from the center of the impact absorbing material. A compression test was conducted on the test piece based on the method specified in JIS K7220:2006, and after a 25% strain was applied to the test piece, the compression load was removed. The magnitude of the strain remaining in the test piece after the load was completely removed was taken as the compression set (unit: %). The compression set values in the examples, comparative examples and reference examples are as shown in Table 2.
[0172] [Table 1]
[0173] [Table 2]
[0174] As shown in Tables 1 and 2, the impact absorbing materials of Examples 1 to 4 are composed of hollow particles with the specific composite resin as the base resin. In addition, the apparent density ρ of these impact absorbing materials, the average particle diameter D of the hollow particles, and the average total thickness t of the resin film in the fusion part are r Therefore, as shown in Table 2, these impact absorbing materials have smaller compression set than the polystyrene resin foamed bead molding (Reference Example).
[0175] In addition, since the impact absorbing materials of Examples 1 to 4 have the above-mentioned specific structure, excessive buckling of the hollow particles constituting the molded body due to an increase in the compression load is suppressed. Therefore, even when the strain amount applied to the impact absorbing material is large, the increase in the load required for deformation is gradual. Therefore, the impact absorbing materials of Examples 1 to 4 have superior energy absorption efficiency when the strain amount is large compared to the impact absorbing material of the reference example.
[0176] The average total thickness of the resin film of the fused portion in the impact absorbing material of Comparative Example 1, t r is smaller than the specific range. Therefore, the impact absorbing material of Comparative Example 1 is more easily deformed than the impact absorbing materials of Examples 1 to 4, and is inferior in energy absorption efficiency both when the amount of strain is large and when the amount of strain is small.
[0177] The average total thickness of the resin film of the fused portion in the impact absorbing material of Comparative Example 2, t r is larger than that of Comparative Example 1, but smaller than the specific range. Therefore, in the impact absorbing material of Comparative Example 2, the hollow particles constituting the molded body are easily buckled with an increase in the compressive load, and when the amount of strain applied to the impact absorbing material increases, the ratio of increase in the load required for deformation relative to the amount of strain increases. As a result, the impact absorbing material of Comparative Example 2 is inferior in energy absorption efficiency when the amount of strain is large compared to the impact absorbing materials of Examples 1 to 4. [Explanation of symbols]
[0178] 1. Shock absorbing material 2 hollow particles 21 Outer shell 22 Hollow part
Claims
1. An impact absorbing material comprising a molded body obtained by molding hollow particles having an outer shell layer and a hollow portion surrounded by the outer shell layer, the shell layer has a resin film having a base resin that is a composite resin containing a (meth)acrylic acid ester component derived from a (meth)acrylic acid ester monomer and a styrene-based component derived from a styrene-based monomer, The apparent density ρ of the impact absorbing material is 20 kg / m 3 More than 100kg / m 3 is as follows: The average particle diameter D of the hollow particles in the impact absorbing material is 2 mm or more and 9 mm or less, The impact absorbing material has a fused portion in which the outer shell layers of the hollow particles are fused to each other, and the average value t of the total thickness of the resin film in the fused portion r is 80 μm or more and 400 μm or less, The average thickness t t of the fused portion is more than 100 μm and 700 μm or less, An impact absorbing material, wherein a ratio t r / t t of an average value t r [μm] of a total thickness of the resin film in the fused portion to an average thickness t t [μm] of the fused portion is 0.3 or more and 0.9 or less.
2. The impact absorbing material according to claim 1, wherein the mass ratio of the (meth)acrylic acid ester component and the styrene-based component contained in the composite resin is (meth)acrylic acid ester component:styrene-based component=70:30 to 30:
70.
3. The apparent density ρ [kg / m 3 )] to the average total thickness t r Ratio t [μm] r / ρ[μm / (kg / m 3 3. The impact absorbing material according to claim 1 or 2, wherein the elastic modulus (Ag) is 2.0 or more and 8.0 or less.
4. The impact absorbing material has a 50% deformation compressive stress σ at 23°C. 50 75% deformation compressive stress σ at 23°C vs. [kPa] 75 Ratio σ of [kPa] 75 / σ 50 The impact absorbing material according to any one of claims 1 to 3, wherein the impact absorbing material has a viscosity of 1.0 or more and less than 2.
0.
5. The impact absorbing material has a 75% deformation compressive stress σ at 23°C. 75 10% deformation compressive stress σ at 23°C vs. [kPa] 10 Ratio σ of [kPa] 10 / σ 75 The impact absorbing material according to any one of claims 1 to 4, wherein the value is 0.30 or more and 1.0 or less.
6. The impact absorbing material according to any one of claims 1 to 5, wherein the impact absorbing material has a compression set of 10% or less.
7. Resin particles used for producing the hollow particles to be used for forming the molded body constituting the impact absorbing material according to any one of claims 1 to 6, A composite resin containing a (meth)acrylic acid ester component derived from a (meth)acrylic acid ester monomer and a styrene-based component derived from a styrene-based monomer is used as a base resin, and the resin particles contain an organic physical blowing agent, The average particle size of the resin particles is 1 mm or more and 5 mm or less, a mass ratio of the (meth)acrylic acid ester component to the styrene-based component contained in the composite resin is (meth)acrylic acid ester component:styrene-based component=70:30 to 30:70; Resin particles, in which a surface absorbance ratio S represented by the following formula (1) in an infrared absorption spectrum of the surface of the resin particles obtained by a total reflection measurement method is 0.70 or more: S=As acryl / As styrene ・・・(1) (However, As in the formula (1) styrene The wave number is 650 cm -1 More than 750cm -1 The maximum absorbance in the range below is As acryl The wave number is 1680 cm -1 1780cm or more -1 The maximum absorbance in the following range:
8. A hollow particle obtained by expanding the resin particle according to claim 7, Bulk density is 20 kg / m 3 More than 100kg / m 3 Below are the hollow particles.
Citation Information
Patent Citations
Hollow spherical foam particle of thermoplastic resin and production of molded article of foam using the same particle
JP1990028225A
Prefoamed particle of thermoplastic resin and production of foam molded article using the same
JP1990107646A
Shock absorbing floor spacer for automobile
JP2003127796A
Expandable thermoplastic resin particle
JP2012197405A
Polystyrene resin particle, method for producing the same, polystyrene resin foam particle and polystyrene resin foam molded body
JP2012201826A